2001
DOI: 10.1111/1469-7610.00806
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Assessment of Children's Attention: The Test of Everyday Attention for Children (TEA‐Ch), Normative Sample and ADHD Performance

Abstract: "Attention" is not a unitary brain process. Evidence from adult studies indicates that distinct neuroanatomical networks perform specific attentional operations and that these are vulnerable to selective damage. Accordingly, characterising attentional disorders requires the use of a variety of tasks that differentially challenge these systems. Here we describe a novel battery, the Test of Everyday Attention for Children (TEA-Ch), comprising nine subtests adapted from the adult literature. The performance of 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
652
3
22

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 619 publications
(708 citation statements)
references
References 74 publications
31
652
3
22
Order By: Relevance
“…Selective attention and attentional control were measured using two subtests, "Map Mission" and "Opposite Worlds, " of the Test of Everyday Attention for Children (24).…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…Selective attention and attentional control were measured using two subtests, "Map Mission" and "Opposite Worlds, " of the Test of Everyday Attention for Children (24).…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…More recently, Deforge, André, Mascoët, Toniolo, Demange, and Fresson ( 2006 ) found defi cits in attention effi ciency in a sample of 71 preterm children (GA between 28 and 36 weeks) at 8 to 10 years. Finally, Bayless and Stevenson ( 2007 ) used the Test of Everyday Attention in Children (Manly, Anderson, Nimmo-Smith, Turner, Watson, & Robertson, 2001 ) to compare the attention and executive functions in a group of forty 6-to 12-yearold preterm children (GA between 28 and 32 weeks) to full-term children. Results showed that preterm children had diffi culties in attention shifting and inhibition.…”
Section: Attentional Network Effi Ciency In Preterm Childrenmentioning
confidence: 99%
“…Subtest, which requires the child to listen to a series of tones presented at irregular intervals over approximately 12 minutes and count them silently, provided a measure of sustained attention. The TEA-Ch has established reliability and validity in assessing aspects of attention and executive functions, and has been used with pediatric TBI (Anderson et al, 1998;Manly et al, 2001). …”
Section: Neuropsychological Batterymentioning
confidence: 99%